A Sign to Heaven: aVR Lead Elevation and Myocardial Infarction - Amir M. Nia; Natig Gassanov; Hannes Reuter; Fikret Er (The Scientific World Journal)
Isolated ST-segment elevation only in the aVR lead, reflecting an acute myocardial infarction due to a left main coronary artery occlusion, was ignored as part of physicians' training in emergency medicine for a long time. The recognition of aVR lead elevation is becoming more accepted as a mandatory diagnostic tool, in particular for physicians working at emergency departments. We report a typical myocardial infarction with total occlusion of the proximal part of the left anterior coronary artery, presenting with ST-segment elevation in the aVR lead, which was misinterpreted as diffuse ischemia. The lacking mandatory awareness of this entity endangered prompt and correct treatment.